Endemicity of chytridiomycosis features pathogen overdispersion. (29th February 2016) - Grogan, Laura F.; Phillott, Andrea D.; Scheele, Benjamin C.; Berger, Lee; Cashins, Scott D.; Bell, Sara C.; Puschendorf, Robert; Skerratt, Lee F.
Summary: Pathogens can be critical drivers of the abundance and distribution of wild animal populations. The presence of an overdispersed pathogen load distribution between hosts (where few hosts harbour heavy parasite burdens and light infections are common) can have an important stabilizing effect on host–pathogen dynamics where infection intensity determines pathogenicity. This may potentially lead to endemicity of an introduced pathogen rather than extirpation of the host and/or pathogen. Overdispersed pathogen load distributions have rarely been considered in wild animal populations as an important component of the infection dynamics of microparasites such as bacteria, viruses, protozoa and fungi. Here we examined the abundance, distribution and transmission of the model fungal pathogen Batrachochytrium dendrobatidis (Bd, cause of amphibian chytridiomycosis) between wild‐caught Litoria rheocola (common mist frogs) to investigate the effects of an overdispersed pathogen load distribution on the host population in the wild. We quantified host survival, infection incidence and recovery probabilities relative to infectious burden, and compared the results of models where pathogen overdispersion either was or was not considered an important feature of host–pathogen dynamics. We found the distribution of Bd load between hosts to be highly overdispersed. We found that host survival was related to infection burden and that accounting for pathogen overdispersion allowed us to better understand infection dynamics and their implications for disease control. In addition, we found that the pattern of host infections and recoveries varied markedly with season whereby (i) infections established more in winter, consistent with temperature‐dependent effects on fungal growth, and (ii) recoveries (loss of infection) occurred frequently in the field throughout the year but were less likely in winter. Our results suggest that pathogen overdispersion is an important feature of endemic chytridiomycosis and that intensity of infection determines disease impact. These findings have important implications for our understanding of chytridiomycosis dynamics and the application of management strategies for disease mitigation. We recommend quantifying individual infectious burdens rather than infection state where possible in microparasitic diseases. Abstract : The authors demonstrate that not only is pathogen overdispersion an important feature of endemic chytridiomycosis (classically considered a microparasitic disease), but that such overdispersion has critical implications for disease dynamics, the ways we model and understand these ecological systems, and for the approaches we take to managing endemically infected animal populations.